2016
DOI: 10.1007/s11010-016-2828-5
|View full text |Cite
|
Sign up to set email alerts
|

High-fructose diet is as detrimental as high-fat diet in the induction of insulin resistance and diabetes mediated by hepatic/pancreatic endoplasmic reticulum (ER) stress

Abstract: In the context of high human consumption of fructose diets, there is an imperative need to understand how dietary fructose intake influence cellular and molecular mechanisms and thereby affect β-cell dysfunction and insulin resistance. While evidence exists for a relationship between high-fat-induced insulin resistance and metabolic disorders, there is lack of studies in relation to high-fructose diet. Therefore, we attempted to study the effect of different diets viz., high-fat diet (HFD), high-fructose diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 51 publications
5
50
1
1
Order By: Relevance
“…High fructose intake produces immediate change in hepatic and extrahepatic substrate metabolism, but the overall glucose production remains unchanged in some reports of human subjects [10] and rodents [11]. More frequently, fasting or postprandial glucose concentrations are increased after high fructose consumption in clinical trials [12] and animal experiments [13]. The elevated glucose output may cause an increase of insulin demand and trigger insulin over-release.…”
Section: Direct Dangerous Factors Under High Fructose Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…High fructose intake produces immediate change in hepatic and extrahepatic substrate metabolism, but the overall glucose production remains unchanged in some reports of human subjects [10] and rodents [11]. More frequently, fasting or postprandial glucose concentrations are increased after high fructose consumption in clinical trials [12] and animal experiments [13]. The elevated glucose output may cause an increase of insulin demand and trigger insulin over-release.…”
Section: Direct Dangerous Factors Under High Fructose Consumptionmentioning
confidence: 99%
“…Impairment of β-cell mass and function inmales with high fructose diets result from dysregulation of leptin signaling and activation of protein kinase B (PKB/Akt)/Forkhead box protein (Fox) O1 in rat islets [15]. ER stress occurs in pancreatic β-cells under high fructose diet, as it is closely associated with insulin resistance, inflammation and abnormal lipid metabolism, possibly leading to glucose intolerance and insulin resistance [13]. …”
Section: Direct Dangerous Factors Under High Fructose Consumptionmentioning
confidence: 99%
“…On the other hand, liver seems to be a key organ in the development of metabolic complications related to fructose-rich diets [21,22,23,24]. Wistar rats were fed diets containing 65% of the calories from fructose, and the accumulation of fat and collagen in the liver tissue was as evident as observed in animals fed a diet rich in saturated fat, promoting apoptosis in this tissue and activation of proteins related to endoplasmic reticulum stress and inflammatory process [21].…”
Section: High Fructose Intake and Its Consequences On Metabolic Hementioning
confidence: 99%
“…Wistar rats were fed diets containing 65% of the calories from fructose, and the accumulation of fat and collagen in the liver tissue was as evident as observed in animals fed a diet rich in saturated fat, promoting apoptosis in this tissue and activation of proteins related to endoplasmic reticulum stress and inflammatory process [21]. Recently, an important study with primates showed that diets rich in fructose were able to induce a hepatic steatosis stage, with lipid droplet size positively correlated to time of exposure to the diet [24].…”
Section: High Fructose Intake and Its Consequences On Metabolic Hementioning
confidence: 99%
“…In a study in rats, fructose induced the mRNA and protein expression of ER stress markers, including GRP-78, PERK, IRE1α, and CHOP in the liver [81]; which on one hand might contribute to the hepatic activation of SREBP-1c and lipid accumulation in fructose-induced NAFLD [38], and on the other hand the increased ER-stress is also suggested to cause hepatic insulin resistance by increasing de novo lipogenesis [10,82]. Another central role of the ER is to control the transport and metabolism of cholesterol, an essential component of cellular membranes, which is mainly regulated by transcription factors of the SREBP family [83].…”
Section: Effect Of Fructose On Metabolic Disturbancesmentioning
confidence: 99%